Manipulation of lesions in patients with cutaneous leishmaniasis: case series in a peruvian hospital - Juan Pineda-Reyes (Revista Peruana de Medicina Experimental y Salud Pública, 2020)
In cutaneous leishmaniasis endemic areas it is a common practice for patients to manipulate their lesions with traditional treatments as a first therapeutic option. A case series study was conducted in order to describe the frequency and the variations of the patient manipulation of cutaneous leishmaniasis lesions at the Cayetano Heredia Hospital. The study included 124 patients with cutaneous leishmaniasis. From the patient population it was found that 54% (67/124) manipulated their lesions. Of this, 92.5% (62/67) did so with chemicals, and 43.3% (29/67) with plants. The most frequent local changes reported by patients were increased lesion size in 35.8% (24/67) and increased inflammation in 28.4% (19/67). Manipulation by patients decreased the positivity of the parasitological diagnosis in those patients with ulcerative lesions.